2009
DOI: 10.1111/j.1398-9995.2008.01921.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double‐blind, placebo‐controlled trial of sublingual immunotherapy with a Pru p 3 quantified peach extract

Abstract: In this first exploratory clinical trial, SLIT for peach allergy seems to be a promising therapeutic option that could modify the clinical reactivity of the patients to peach intake and the underlying immunological response with a good tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
154
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(167 citation statements)
references
References 33 publications
9
154
0
4
Order By: Relevance
“…Despite the data suggesting comparable events for AIT to food allergens as compared to inhalant allergens (Table 1), there is eminent need to understand the induction of immunological pro-tolerogenic events at a cellular and humoral level to food allergens to delineate desensitization from tolerance development (77,88,99) (Table 1).…”
Section: Oral and Sublingual Immunotherapy In Food Allergymentioning
confidence: 99%
“…Despite the data suggesting comparable events for AIT to food allergens as compared to inhalant allergens (Table 1), there is eminent need to understand the induction of immunological pro-tolerogenic events at a cellular and humoral level to food allergens to delineate desensitization from tolerance development (77,88,99) (Table 1).…”
Section: Oral and Sublingual Immunotherapy In Food Allergymentioning
confidence: 99%
“…Sublingual immunotherapy (SLIT) is another potential route of administration and has been investigated for hazelnut (84,85) and peach allergy (86). Both studies demonstrated increased tolerance after 5-6 months of treatment.…”
Section: Allergen-specific Therapiesmentioning
confidence: 99%
“…Following standard recommendations a four vials (0.05, 0.5, 5 and 50 µg/ml of Pru p3-Peach peel LTP) and days rush schedule was applied. From an initial dose of 0.242 µg of Pru p3 the first day, the maintenance dose consisted of 10 µg of Pru p3 everyday [5]. Immunotherapy was maintained for four months with good tolerance, the only relevant secondary effect was light oral pruritus with the first doses, which was solved with antihistamines.…”
Section: Short Communicationmentioning
confidence: 99%
“…Subsequently we undertook an open oral challenge with lentil and chickpea. We used lentil and chickpea soups in progressively increasing doses (1,5,10,30,75, and 125 mL) every 15 minutes according to previous studies [6]. Both challenges were negative.…”
Section: Short Communicationmentioning
confidence: 99%